Nucleic Acids Delivery Into the Cells Using Pro-Apoptotic Protein Lactaptin - Chinak, Olga; Golubitskaya, Ekaterina; Pyshnaya, Inna; Stepanov, Grigory; Zhuravlev, Evgenii; Richter, Vladimir; Koval, Olga (Frontiers in Pharmacology, 2019)
Cell penetrating peptides (CPP) are promising agents for transporting diverse cargo into the cells. The amino acid sequence and the mechanism of lactaptin entry into the cells allow it to be included into CPP group. Lactaptin, the fragment of human milk kappa-casein, and recombinant lactaptin (RL2) were initially discovered as molecules that induced apoptosis of cultured cancer cells and did not affect non-malignant cells. Here, we analyzed the recombinant lactaptin potency to form complexes with nucleic acids and to act as a gene delivery system. To study RL2-dependent delivery, three type of nucleic acid were used as a models: plasmid DNA (pDNA), siRNA, and non-coding RNA which allow to detect intracellular localization through their functional activity. We have demonstrated that RL2 formed positively charged noncovalent 110-nm-sized complexes with enhanced green fluorescent protein (EGFP)-expressing plasmid DNA. Ca2+ ions stabilized these complexes, whereas polyanion heparin displaced DNA from the complexes. The functional activity of delivered nucleic acids were assessed by fluorescent microscopy using A549 lung adenocarcinoma cells and A431 epidermoid carcinoma cells. We observed that RL2:pDNA complexes provided EGFP expression in the treated cells and that strongly confirmed the entering pDNA into the cells. The efficiency of cell transformation by these complexes increased when RL2:pDNA ratio increased. Pre-treatment of the cells with anti-RL2 antibodies partly inhibited the entry of pDNA into the cells. RL2-mediated delivery of siRNA against EGFP was analyzed when A549 cells were co-transfected with EGFP-pDNA and RL2:siRNA complexes. siRNA against EGFP efficiently inhibited the expression of EGFP being delivered as RL2:siRNA complexes. We have previously demonstrated that non-coding U25 small nucleolar RNA (snoRNA) can decrease cell viability. Cancer cell transfection with RL2-snoRNA U25 complexes lead to a substantial decrease of cell viability, confirming the efficiency of snoRNA U25 delivery. Collectively, these findings indicate that recombinant lactaptin is able to deliver noncovalently associated nucleic acids into cancer cells in vitro.